INOVASI PROGRAM ANJUNGAN DUKCAPIL MANDIRI DALAM MENINGKATKAN KUALITAS PELAYANAN PUBLIK ADMINISTRASI KEPENDUDUKAN : (Studi Pada Dinas Kependudukan dan Pencatatan Sipil Kabupaten Malang) - Dinda Septiana; Hayat; Langgeng Rachmatullah Putra (Journal Publicuho, 2022)
The purpose of this study was to find out the Innovation of the Mandiri Civil Registry Pavilion Program in Improving the Quality of Population Administration Public Services at the Department of Population and Civil Registration of Malang Regency. This study uses a descriptive qualitative approach through interactive data analysis according to Miles Huberman and Saldana (2014). The results of the study show that ADM has a service system that is different from direct service because it connects between networks where the service is sufficient via online in managing population administration which acts as a link to be able to access printing to use ADM machines. In this program innovation is in accordance with public service innovation indicators which show changes in the system and form of population administration services. Supporting factors for this ADM program innovation include ADM machine operators in each sub-district, socialization support and easy access. While the inhibiting factors are the limited facilities and infrastructure, and the lack of understanding of the community.